Analysis Of Data Climate The Several Town In Indonesia For Support The Development Of Standard Adaptive Comfort The Traditional Homes. - Wahyu Sujatmiko; Amat Rahmat; Karto Wijaya (Universitas Kebangsaan Republik Indonesia [UKRI], 2019)
ABSTRACT : According to the adaptive thermal comfort approach, the neutral temperatures or the comfortable temperature of building occupants can be predicted based on the average data of the outdoor air temperature in the vicinity of the residential buildings. Generally the residents of the residential buildings still feel comfortable in the range of zones 80% or plus minus two and a half degrees of comfortable temperature.This paper attempts to analyze the typical annual climate data was published by ASHRAE RP 1477 in the Year 2011 for the purpose of estimating the comfort zone of traditional buildings in Indonesia. The method was used is the statistical data processing of 28 cities in Indonesia, to be presented in the form of average, minimum, maximum, daily and monthly data. It is expected that this method will get selected daily data profile and monthly data. Furthermore, the monthly data calculated comfort zone follows the adaptive thermal equation of ASHRAE 55 2004.The existing data are expected later to be used to compare with the actual data of mean vote which have accumulated over several years of this measurement for prediction the comfort level of the existing traditional dwelling.Keywords : Typical Annual Climate Data; Adaptive Thermal Comfort; ASHRAE; Traditional Buildings; Natural Ventilation